Recognition of the Impact of Artificial Intelligence on Patent Law of the European Union - Phuong, Dang Minh; Ha, Nguyen Nhu (VNU Journal of Science: Legal Studies; Vol 38 No 3, 2022)
Artificial intelligence has been paving the way for revolutionizing science, technology and production worldwide, and at the same time entailing changes in traditional legal relations – patent law is not outside the scope of influence of artificial intelligence. Questions are being raised about the increasing patent protection system such as the object of an invention, the subject of an invention or the criteria for evaluating patentability. The article provides an insight into the experience of the European Union patent law in response to the effects of artificial intelligence, thereby proposing some recommendations for Vietnam.